Comparison of Glyaderm with different dermal substitute matrices in a porcine wound model. (December 2022) - Pirayesh, Ali; De Decker, Ignace; Richters, Cornelia D.; Paauw, Nanne J.; Hoeksema, Henk; Hoekstra, Matthias J.; Claes, Karel E.Y.; Van Der Lei, Berend; Monstrey, Stan
Abstract: Background: The closure of extensive burn wounds with widely expanded autologous split-thickness skin grafts (STSG) is associated with undesirable scar formation and contraction, due to the lack of dermis. Various materials for dermal replacement have been developed, either of xenogeneic, allogeneic or synthetic origin and are placed in the wound underneath a thin STSG in order to improve scar quality. In this study, a porcine wound model was used to compare several commercially available acellular dermal substitutes with an acellular dermal substitute prepared from glycerol preserved human skin: Glyaderm Ⓡ . Methods: Antigenic components of the allografts were removed by incubation in the 0.06 M NaOH solution. In the first experiments, the dermal substitutes were applied to full thickness wounds and covered simultaneously with STSG. Controls were covered with STSG only. The wound healing response was analyzed for 8 weeks, both macroscopically and histologically. The Mann-Whitney U test was used for statistical analysis. In the second series of experiments, Glyaderm Ⓡ was applied in a two-stage procedure in comparison to Integra. The STSG was placed on the dermal substitutes one week later. Results: In the first series, the inflammatory response and myofibroblast influx in Glyaderm Ⓡ were limited, indicating possible beneficial outcomes on final wound healing results. The survival of the STSG on the acellular dermis was lower compared to the control wounds. Second series: the take of the STSG was the same as in the controls, but additionally wound contraction was reduced. The application of Glyaderm Ⓡ was non-inferior to Integra. Conclusion: Glyaderm Ⓡ can be successfully used for the reduction of wound contraction when applied in a two-stage procedure.